ANALYSIS OF PROFITABILITY, COMPANY SIZE, SALES GROWTH AND BUSINESS RISK ON CAPITAL STRUCTURE - Berlian Karlina; Dwi Juliyanti (MESP–FEB UNS, 2021)
This study aims to determine the effect of Profitability, Size, Sales Growth and Business Risk on the Capital Structure of the Food and Beverage Sub-Sector Companies listed on the Indonesia Stock Exchange (IDX) for the period 2015-2019. The sampling technique uses a sampling method the study population was 33 companies and the sample used was 15 companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange. The method used in this research is the hypothesis testing method (Hypothesis Testing). The analytical tool used is multiple linear regression analysis tested using the Statistical Package for the Social Science (SPSS) Version 25 program. The data used are secondary data in the form of complete financial reports during the study period. The results of this study indicate that the Profitability variable has a significant effect on capital structure, while the variables of company size, sales growth and business risk have no significant effect on capital structure. Keywords: Profitability, Size, Sales Growth, Business Risk and Capital Structure